Effectiveness of the 5E Learning Cycle Model Assisted by Worksheets in Teaching Exponents at the Secondary School Level: A Quasi-Experimental Study - Devinda Putri Maharani (Journal of Blended and Technical Education, 2026)
Objective: This study aims to analyze the effectiveness of the 5E Learning Cycle Model, supported by worksheets media, on students’ learning outcomes in the topic of exponents. Research Design & Methods: This study employs a quantitative approach using a quasi-experimental method with a Non-Equivalent Control Group Design. The study population consists of 60 eleventh-grade students at SMK Kholiliyah Bangsri for the 2025/2026 academic year, with a sample of 52 students selected using cluster random sampling. The sample consisted of an experimental class that received instruction using the 5E Learning Cycle Model supported by worksheets and a control class that used conventional instruction. Data collection techniques included tests, observations, and documentation. Data analysis was conducted using descriptive statistics, normality tests, homogeneity tests, and the Paired Sample t-Test. Findings: The results of the study indicate that the implementation of the 5E Learning Cycle Model supported by worksheets is effective in improving student learning outcomes. The average pretest score of the experimental class increased from 54.23 to 84.65 on the posttest. The results of the Paired Sample t-Test showed a significance value of 0.000 < 0.05, indicating a significant difference between learning outcomes before and after the intervention. Contributions: This study contributes to the development of constructivist-based mathematics learning through the implementation of the 5E Learning Cycle Model supported by worksheets. Novelty: This study extends constructivist learning research by providing empirical evidence that the 5E Learning Cycle Model supported by worksheets improves students' conceptual understanding of exponentiation.